Evaluation of two different CAD-CAM inlay-onlays in a split-mouth study: 2-year clinical follow-up - ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT (WILEY, 2020)
Objective To evaluate the clinical performance of hybrid ceramic inlay-onlay restorations over a 2-year period. Clinical Considerations A total of 30 lithium disilicate glass ceramic (LDC; control group) and 30 hybrid ceramic (HC; test group) inlay/onlay restorations were performed in 14 patients. Clinical evaluations were performed after 1 week, 6 months, 1 year, and 2 years of cementation according to the modified United States Public Health Service (USPHS) criteria, gingival index, and plaque index. The Friedman test was used for the significant difference in time and Wilcoxon signed-rank test was used for the determination of differences. The clinical parameters, gingival and plaque indexes differences in time were analyzed with Chi-square test. No statistically significant difference (P > .05) was found between the two groups in the modified USPHS, gingival index, and plaque index evaluations, whether statistically significant differences were found within groups. The total survival rate was 100% for both groups after 2 years. Conclusion Based on the 2-year data, the tested HC can be considered a reliable material for inlay/onlay restorations. Clinical Significance The results of this in vivo study suggest that both resin nanoceramic materials and LDC materials have been successfully incorporated in treatments of inlay and onlay restorations. Short-term results showed that resin nanoceramic materials can be counted as a good choice in inlay and onlay restorations in an effort to reduce the treatment time associated with ceramic firing processes.
Keywords: CAD-CAM restorations; hybrid ceramics; lithium disilicate glass ceramics; onlay restorations; split-mouth study; GLASS-CERAMIC INLAYS; CEREC CAD/CAM INLAYS; MARGINAL ADAPTATION; COMPOSITE RESTORATIONS; CALCIUM HYDROXIDE; INTERNAL FIT; CROWNS; PERFORMANCE; ACCURACY; SYSTEMS